2016
DOI: 10.1021/acs.est.6b02661
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Characterization of Iron Oxide–Aqueous Fe2+ Redox Couples

Abstract: Iron is present in virtually all terrestrial and aquatic environments, where it participates in redox reactions with surrounding metals, organic compounds, contaminants, and microorganisms. The rates and extent of these redox reactions strongly depend on the speciation of the Fe2+ and Fe3+ phases, although the underlying reasons remain unclear. In particular, numerous studies have observed that Fe2+ associated with iron oxide surfaces (i.e., oxide-associated Fe2+) often reduces oxidized contaminants much faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
173
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(197 citation statements)
references
References 79 publications
23
173
1
Order By: Relevance
“…4 for better demonstration of iron mineral reductions as their reduction potentials lay in between. Magnetite and hematite minerals showed a very similar reduction potential that ranged from −150 to −100 mV versus SHE from a high to low scan rate, which was consistent with previously reported potentials (about −200 to −120 mV versus SHE) obtained by thermodynamic calculations and microbial mineral reduction414243. The observed reduction rate (the rate was normalized by the mineral surface area, Fig.…”
Section: Resultssupporting
confidence: 90%
“…4 for better demonstration of iron mineral reductions as their reduction potentials lay in between. Magnetite and hematite minerals showed a very similar reduction potential that ranged from −150 to −100 mV versus SHE from a high to low scan rate, which was consistent with previously reported potentials (about −200 to −120 mV versus SHE) obtained by thermodynamic calculations and microbial mineral reduction414243. The observed reduction rate (the rate was normalized by the mineral surface area, Fig.…”
Section: Resultssupporting
confidence: 90%
“…56,57 Alternatively, mediated electrochemical techniques make use of dissolved redox active compounds, which facilitate electron transport between mineral and electrode. 58 Consequently, through various theoretical and measurement based techniques, 58,59 the standard redox potentials of a number of different Fe(III) minerals have been determined for their reduction to Fe(II) ( Table 3). reduction" refers to experimental quantification of ferrous iron after reduction of minerals with H2; 59 "Mediated potentiometry" refers to values obtained by measuring redox potential of mineral suspensions using a Pt redox electrode in the presence of a soluble electron transfer mediator.…”
Section: Redox Potentialmentioning
confidence: 99%
“…3 (red straight line) and we found that the parameter E 0 = 1120 mV. This value is higher than the theoretical equilibrium potential for the reaction (3): E 0 = 937 mV (Gorski et al 2016). Probably, the determined value of E 0 is a mixed potential of two or more redox processes like the oxygen reduction to water with equilibrium potential of E 0 = 1230 mV (compare with Figure 8.28b in the reference (Stumm and Morgan 1996)).…”
Section: Resultsmentioning
confidence: 50%
“…In natural waters dissolved iron can exist as Fe 2+ ion with combination with Fe 3+ oxides and hydroxides (Stumm and Morgan 1996). Therefore, the reactions between dissolved Fe 2+ ions and iron(III) oxides were thoroughly studied both experimentally and theoretically (Dixit and Hering 2006;Gorski and Scherer 2011;Gorski et al 2016;Kerisit et al 2015;Larese-Casanova et al 2012;Larese-Casanova and Scherer 2007;Tanwar et al 2008;Rosso 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation